Euroepan landscape sin Transition - implications for policy and practice - Pinto-Correia, Teresa (2019)
European rural landscapes have been our common research area for years. Based on each of our research projects and involvement with local landscapes and landscape agents, we have experienced how change patterns and the policies that guide them have been transformed, although not always in ways that properly address the new dynamics. These insights formed our main motivation for writing this book together. It is the result of a three-year journey into the literature and concrete examples of landscape transitions and policy initiatives and not least our joint reflections and numerous discussions on change patterns, concepts, frameworks, and policy approaches. We hope that academics, policy makers, planners, and students who are seeking to better understand and manage the transitions processes of European rural landscapes will find the book useful. The European continent is highly diverse with rich natural and cultural histories and the rural landscapes reflect this diversity. In fact, the variety and heterogeneity of the landscapes, both at the regional and local scale, to a large extent characterizes the European continent. This complexity makes it difficult to generalize and identify common ground for research and the practical management of European landscapes. We have tried to balance our analyses and suggestions between generalized approaches and concrete examples and we hope that we have captured the main topics concerning Europe’s current transitions and policy challenges. During our research, we have benefitted greatly from critical comments, constructive suggestions, practical support and assistance from many individuals and institutions. The three of us share the privilege of working for academic institutions which provide opportunities for conducting work like this. Therefore, we are grateful to ICAAM, the Institute for Mediterranean Agrarian and Environmental Sciences, the University of Évora, the Department of Geosciences and Natural Resource Management, the University of Copenhagen, and to Alterra and Wageningen University for providing the practical conditions for writing the book. Thanks also to the mains sponsors of the Future Landscapes programme: Realdania Foundation, Nordea Foundation, 15th June Foundation and the Danish Outdoor Council for enabling us to start the work with a series of public lectures in Denmark on European landscapes in transition. Thanks also to Sara Folvig for preparing several of the figures, to Stuart Wright for his excellent work on enhancing our non-native English, and to Victoria Parrin, Kirsten Bot and Dominic Lewis from Cambridge University Press who have been of great help in preparing the manuscript for publication as well as being generously patient. Simon Swaffield’s and two anonymous reviewers’ comments on the original book proposal were also greatly appreciated. Each of the book chapters was reviewed by colleagues and, therefore, we would like to thank Marc Antrop, Peter Howard, Gertrud Jørgensen, Søren Pilgaard Kristensen, Mattias Qvistström, Simon Swaffield, Richard Wakeford, Karlheinz Knickel and Anders Wästfelt for their critical and constructive comments on the chapters. We have included numerous examples of specific landscapes and the changes they are currently undergoing in the book. These are presented at the start of each chapter, in text boxes, and in the form of 8 case studies. Three of these cases were provided by colleagues and our sincere thanks go to Janez Pirnat, University of Ljubljana, Slovenia, and Diana Surova and Jose Munoz-Rojas, ICAAM, University of Évora, who generously gave us the opportunity to include the cases in the book..